Ownership versus management : the role of farming networks in Argentina - Senesi, Sebastián Ignacio (2017)
Fil: Senesi, Sebastián Ignacio. Universidad de Buenos Aires. Facultad de Agronomía. Programa de Agronegocios (PAA). Buenos Aires, Argentina.